Microencapsulation Approach For Anti-Inflammatory Treatment: Drug Release Kinetics, Antibacterial Potential, And Intestinal Microbiota Evaluation (International Journal of Environmental Sciences, 2025)
The objective of this study was to evaluate the potential of a microencapsulated diclofenac formulation to prevent inflammation-induced alterations in the intestinal microbiota while minimizing systemic side effects. Diclofenac was encapsulated in an ethylcellulose-based microparticulate system using an oil-in-water (O/W) emulsion–evaporation method. The study examined the physicochemical properties of the microparticles, in vitro drug release behavior, antimicrobial activity, and in vivo anti-inflammatory efficacy, as well as their impact on gut microbiota composition. The resulting spherical microparticles, characterized by scanning electron microscopy (SEM), exhibited variable porosity, an average Sauter diameter of 292 µm, and a drug-loading efficiency of 32%. FTIR and XRD analyses confirmed the presence of the active compound. In vitro release kinetics followed a quasi-Fickian diffusion mechanism, consistent with the Higuchi model. The released drug demonstrated antimicrobial activity against Escherichia coli, Staphylococcus aureus, and Bacillus cereus In vivo testing in Wistar rats identified 6.42 mg as the effective anti-inflammatory dose in a paw-edema model. Fecal microbiota analysis revealed that treatment with the encapsulated drug modulated the abundance of specific bacterial populations, suggesting an influence on gut microbial balance. These results demonstrate that microencapsulation via O/W emulsion–evaporation can enhance diclofenac’s anti-inflammatory efficacy, provide controlled drug release, and influence intestinal microbiota, offering a promising strategy for improved therapeutic interventions.